Osteoprotective Roles of Green Tea Catechins - Hsuan-Ti Huang; Tsung-Lin Cheng; Sung-Yen Lin; Cheng-Jung Ho; Joanna Y. Chyu; Rong-Sen Yang; Chung-Hwan Chen; Chwan-Li Shen (MDPI AG, 2020)
Osteoporosis is the second most common disease only secondary to cardiovascular disease, with the risk of fracture increasing with age. Osteoporosis is caused by an imbalance between osteoblastogenesis and osteoclastogenesis processes. Osteoclastogenesis may be enhanced, osteoblastogenesis may be reduced, or both may be evident. Inflammation and high reactive oxygen enhance osteoclastogenesis while reducing osteoblastogenesis by inducing osteoblast apoptosis and suppressing osteoblastic proliferation and differentiation. Catechins, the main polyphenols found in green tea with potent anti-oxidant and anti-inflammatory properties, can counteract the deleterious effects of the imbalance of osteoblastogenesis and osteoclastogenesis caused by osteoporosis. Green tea catechins can attenuate osteoclastogenesis by enhancing apoptosis of osteoclasts, hampering osteoclastogenesis, and prohibiting bone resorption in vitro. Catechin effects can be directly exerted on pre-osteoclasts/osteoclasts or indirectly exerted via the modulation of mesenchymal stem cells (MSCs)/stromal cell regulation of pre-osteoclasts through activation of the nuclear factor kB (RANK)/RANK ligand (RANKL)/osteoprotegerin (OPG) system. Catechins also can enhance osteoblastogenesis by enhancing osteogenic differentiation of MSCs and increasing osteoblastic survival, proliferation, differentiation, and mineralization. The in vitro effects of catechins on osteogenesis have been confirmed in several animal models, as well as in epidemiological observational studies on human subjects. Even though randomized control trials have not shown that catechins provide anti-fracture efficacy, safety data in the trials are promising. A large-scale, placebo-controlled, long-term randomized trial with a tea regimen intervention of optimal duration is required to determine anti-fracture efficacy.